Transoral penetrating craniocerebral injury: a case report and literature review - Xue, Hang; Li, Wei; Zhang, Weitao; Sun, Lei; Li, Yubo; Yang, Hongfa (Frontiers in Surgery, 2024)
A penetrating brain injury is a rare type of neurosurgical trauma associated with extremely high mortality and disability rates. Penetrating skull base injuries caused by arrows seldom occur because injuries caused by such weapons are more likely to be accidental. However, the number of self-inflicted injuries is increasing, and these injuries have varying patterns and high mortality rates. We report a case of a transoral penetrating craniocerebral injury caused by an arrow in a suicidal patient. Preoperative imaging is crucial for detecting and planning the surgical approach. Surgery is an effective treatment for this type of injury. Additionally, we reviewed previous case reports on this type of injury to provide recommendations for its clinical detection and treatment.